Sustainability in African Higher Education Institutions and the influence of language in achieving sustainable development - Ulmer, Nico (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2024)
This thesis deals with sustainability in African Higher Education Institutions (HEIs) and the influence of language in achieving sustainable development. Several authors highlight the existing imbalance of sustainability research in higher education, with most publications focusing on the so-called Global North. Little is known about sustainability in the so-called Global South, and in African educational institutions in particular. The first article of this thesis investigated existing sustainability activities in African HEIs. Rather than focusing on the shortcomings, the paper took a positive stance, opposing the predominant language of deficits in research on Africa. In the Delphi study conducted, 32 experts from 29 HEIs in 16 African countries described the sustainability activities they are engaging in. Experts provided information about their experiences in their respective HEI, while language and culture emerged as areas in need of further research. The second article therefore focused on the relationship between language and education for sustainable development in African educational institutions, and systematically reviewed scholarly literature regarding this connection. Authors of the reviewed 33 papers approached this connection mainly on a theoretical and philosophical level, focusing on education and Africa as a whole rather than specified forms of education in specific countries. The third article examined the views of Tanzanian higher education students and graduates regarding language and sustainability. Participants explained how they integrate sustainability and the Sustainable Development Goals (SDGs) into their research and how they approach translations in the process. In the ensuing interviews, participants estimated that only a fraction of people outside of academia are aware of sustainability and the SDGs, rendering the achievement of target 4.7 unlikely. This thesis therefore contributes to a better understanding of the current challenges in implementing sustainability and the SDGs in African educational institutions. It highlights the need to integrate (local) African languages in order for sustainability activities as well as the SDGs to be successful.

Diese Dissertation behandelt Nachhaltigkeit in afrikanischen Hochschuleinrichtungen (HEIs), mit einem besonderen Fokus des sprachlichen Einflusses zur Erreichung einer Nachhaltigen Entwicklung. Verschiedene Autoren heben das bestehende Ungleichgewicht in der Nachhaltigkeitsforschung im Hochschulsektor hervor. Die meisten wissenschaftlichen Veröffentlichungen konzentrieren sich aber auf den sogenannten Globalen Norden. Über Nachhaltigkeit im sogenannten Globalen Süden ist dagegen wenig bekannt, was insbesondere für afrikanische Bildungseinrichtungen gilt. Der erste Artikel dieser Dissertation untersucht daher existierende Nachhaltigkeitsaktivitäten in afrikanischen HEIs. Gegenüber der üblichen "Sprache der Defizite", die in Forschung zu Afrika vorherrscht, nahm diese Forschung einen positiven Ansatz ein. An der Delphi-Studie nahmen 32 Experten aus 29 HEIs in 16 afrikanischen Ländern teil und gaben Auskunft über die Nachhaltigkeitsaktivitäten in ihrer jeweiligen Hochschuleinrichtung. Hierbei kristallisierten sich die Themenkomplexe Sprache sowie Kultur als weitere Forschungsbereiche heraus. Der zweite Artikel konzentrierte sich daher auf die Beziehung zwischen Sprache und Bildung für nachhaltige Entwicklung in afrikanischen Bildungseinrichtungen, und untersuchte diesen Zusammenhang anhand einer Systematischen Literatur Review. Autoren der analysierten 33 Artikel näherten sich diesem Zusammenhang überwiegend auf theoretischer und philosophischer Ebene. Ferner lag der Schwerpunkt in den analysierten Artikeln auf genereller Bildung und Afrika als Ganzem, anstatt auf spezifischen Bildungsebenen in einzelnen Ländern. Der dritte Artikel untersuchte daher die Erfahrungen tansanischer Hochschulstudenten und Hochschulabsolventen in Bezug auf Sprache und Nachhaltigkeit in einer Fallstudie. Die Teilnehmenden erläuterten, wie sie Nachhaltigkeit und die Sustainable Development Goals (SDGs) in ihre Forschung einbeziehen und diese Leitbilder von Englisch ins Swahili übersetzen. In den anschließenden Interviews schätzten die Teilnehmenden, dass nur ein Bruchteil der Menschen außerhalb des akademischen Betriebes von Nachhaltigkeit und den SDGs gehört haben, was das Erreichen von Ziel 4.7 der SDGs unwahrscheinlich macht. Diese Dissertation trägt daher zu einem besseren Verständnis hinsichtlich der bestehenden Herausforderungen der Nachhaltigkeitskommunikation in Afrikanischen Bildungseinrichtungen bei und unterstreicht die Notwendigkeit, (lokale) afrikanische Sprachen in den Prozess zu integrieren.
Nachhaltigkeit in afrikanischen Hochschuleinrichtungen und der Einfluss von Sprache auf das Erreichen einer nachhaltigen Entwicklung
Keywords: 378 Hochschulbildung